2014
DOI: 10.1186/1471-2474-15-361
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Disabilities of the Arm, Shoulder and Hand (DASH) with Dupuytren’s contracture: validity evidence using Rasch modeling

Abstract: BackgroundDupuytren’s contracture is a progressive, fibroproliferative disorder that causes fixed finger contractures and can lead to disability. With the advances of new therapeutic interventions, the necessity to assess the functional repercussions of this condition using valid, reliable and sensitive outcome measures is of growing interest. The Disabilities of the Arm, Shoulder and Hand (DASH) is one frequently used patient-reported outcome measure but its reliability and validity have never been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 60 publications
2
53
2
2
Order By: Relevance
“…Meanwhile, gender contributed significantly to physical function (p < .001) and symptoms/social function (p D .028), and women reported higher degrees of physical disability and symptoms than men. Similar results were found in studies conducted by Cheng et al 38 and Forget et al 33 Greenslade et al, 40 Jester et al, 41 and Forget et al 33 reported that these results might be explained by the items in the instrument because most items were related to domestic activities, which were primarily performed by women, including making the bed and domestic tasks. According to Hooftman et al, 42 a similar exposure to the same risk factor among men and women may have a greater effect on women due to biological differences (body size, muscular capacity, aerobic capacity, and hormonal conditions) or to psychological differences (such as coping strategies).…”
Section: Commentsupporting
confidence: 83%
See 2 more Smart Citations
“…Meanwhile, gender contributed significantly to physical function (p < .001) and symptoms/social function (p D .028), and women reported higher degrees of physical disability and symptoms than men. Similar results were found in studies conducted by Cheng et al 38 and Forget et al 33 Greenslade et al, 40 Jester et al, 41 and Forget et al 33 reported that these results might be explained by the items in the instrument because most items were related to domestic activities, which were primarily performed by women, including making the bed and domestic tasks. According to Hooftman et al, 42 a similar exposure to the same risk factor among men and women may have a greater effect on women due to biological differences (body size, muscular capacity, aerobic capacity, and hormonal conditions) or to psychological differences (such as coping strategies).…”
Section: Commentsupporting
confidence: 83%
“…We used the classical theory for process validation, although Franchignoni et al, 31 Cano et al, 32 and Forget et al 33 consider the Rasch analysis a more robust method. In the present study, 3 factorial proposals were tested for the DASH scale (uni, bi, and trifactorial), and since the Rasch analysis considers unidimensionality to be an important assumption, its use would not be feasible.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, she had sprain or subluxation of the elbows and ankles countless times and had sustained dislocation of the knees, which had to be treated surgically, several times. Even though her father had Dupuytren's contracture, a chronic, progressive, fibroproliferative disorder of the palm with a predilection for men, 7 and her older brother was also suspected of having EDS, they had only mild symptoms of ankle sprains.…”
Section: Discussionmentioning
confidence: 99%
“…DASH может помочь в оценке расстройств бытовых навыков, с которыми сталкиваются пациенты, а также подходит для длительного мониторин-га состояния больного. Опросник применим для исследо-вательских и клинических целей [41][42][43]. DASH может обнаруживать большие и малые изменения неспособно-сти с течением времени, при этом разницу в показателях в пределах 10 пунктов можно рассматривать как минималь-но важные изменения [44,45].…”
Section: опросник неспособности верхней конечности (Dash)unclassified